PENGARUH METODE CASH ON DELIVERY (COD) TERHADAP MINAT BELI DI SHOPEE (STUDI KASUS DI KP PILAR LEUWISADENG BOGOR) - Larissa, Fanya Alifia; Novita, Evi; Sukarna (Economics Learning Experience & Social Thinking Education Journal, 2025)
This research is motivated by the growing development of payment methods for digitalized transactions, one of which is the Cash On Delivery (COD) payment method. Then the problem arose because he saw the habit of online transactions using the Cash On Delivery method carried out by the people of Kp Pilar Leuwisadeng Bogor. The purpose of this study was to determine the effect of the Cash On Delivery payment method on people's buying interest in e-commerce Shopee at Kp Pilar Leuwisadeng Bogor. This study uses a quantitative approach. The data collection technique used was a questionnaire with a population of 455 and a sample of 69 people with an age range of 15-40 years. The results showed that there was a significant relationship between the effect of the Cash On Delivery payment method on the buying interest of the people of Kp Pilar Leuwisadeng Bogor with a tcount of 3.287 > ttable of 1.668 and a sig. 0.002 <0.05, means that the alternative (Ha) is accepted.